Menemukan Makna “Sekolah” dalam Ibadah Sekolah Minggu dan Relevansinya sebagai Liturgi Anak (Children’s Liturgy) - Yuniar Mariska Simamora (PEADA': Jurnal Pendidikan Kristen, 2025)
Abstract: Studies on Sunday School have generally been situated within a pedagogical framework that emphasizes biblical instruction, teaching methods, and the achievement of children's faith formation goals. In contrast, scholarship on Children's Liturgy has developed within a different discourse, focusing on children's participation in the worshiping life of the church. As a result, the relationship between faith education and children's liturgical experience has rarely been explored in an integrated manner. This study seeks to re-examine the meaning of the term “school” in Sunday School through the perspective of Children's Liturgy. Employing a literature review methodology, the study examines various sources on the history of Sunday School, child pedagogy, child theology, and liturgical theology. The findings indicate that the meaning of “school” in Sunday School cannot be reduced to a mere space for the transmission of religious knowledge; rather, it should be understood as a space for faith formation that integrates both pedagogical and liturgical dimensions. From the perspective of child theology, children are subjects of faith and full members of the church community who are called to participate in its liturgical life. Accordingly, Sunday School may be understood as Children's Liturgy—a formative worship space in which children experience, respond to, and embody God's work through prayer, Scripture, symbols, songs, rituals, and participation in the faith community. The originality of this study lies in its integration of child pedagogy and children's liturgy within a conceptual framework that positions Sunday School as a liturgical practice that is inherently pedagogical. Abstrak: Kajian tentang Sekolah Minggu selama ini umumnya ditempatkan dalam kerangka pedagogis yang menekankan pengajaran Alkitab, metode pembelajaran, dan pencapaian tujuan pendidikan iman anak. Sementara itu, kajian mengenai Children’s Liturgy berkembang dalam diskursus yang berbeda dengan fokus pada partisipasi anak dalam kehidupan ibadah gereja. Akibatnya, relasi antara pendidikan iman dan pengalaman liturgis anak belum banyak dipahami secara integratif. Penelitian ini bertujuan mengkaji ulang makna “sekolah” dalam Sekolah Minggu melalui perspektif Children’s Liturgy. Metode yang digunakan adalah studi literatur dengan menelaah berbagai sumber mengenai sejarah Sekolah Minggu, pedagogik anak, teologi anak, dan teologi liturgi. Hasil kajian menunjukkan bahwa makna “sekolah” dalam Sekolah Minggu tidak dapat direduksi menjadi ruang transmisi pengetahuan agama semata, tetapi perlu dipahami sebagai ruang formasi iman yang mengintegrasikan dimensi pedagogis dan liturgis. Dalam perspektif teologi anak, anak merupakan subjek iman dan anggota penuh komunitas gereja yang dipanggil untuk berpartisipasi dalam kehidupan liturgis. Karena itu, Sekolah Minggu dapat dipahami sebagai Children’s Liturgy, yaitu ruang ibadah formatif tempat anak mengalami, merespons, dan menghidupi karya Allah melalui doa, firman, simbol, nyanyian, ritual, serta kehidupan komunitas iman. Kebaruan penelitian ini terletak pada integrasi kajian pedagogik dan liturgi anak dalam kerangka yang menempatkan Sekolah Minggu sebagai praktik liturgis yang secara inheren bersifat pedagogis.